2003
DOI: 10.1373/clinchem.2003.022541
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C-III Isofocusing in the Diagnosis of Genetic Defects in O-Glycan Biosynthesis

Abstract: Background: Defects in the biosynthesis of N-glycans may be found by isoelectric focusing (IEF) of plasma transferrin. No test is available to demonstrate O-glycan biosynthesis defects. Methods: We used isoforms of apolipoprotein C-III (apoC-III) as a marker for the biosynthesis of core 1 mucin type O-glycans. Plasma samples from patients with primary defects and secondary alterations in Nglycan biosynthesis were studied by apoC-III isofocusing. Results: Age-related reference values for apoC-III were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 30 publications
(17 reference statements)
4
81
0
Order By: Relevance
“…IEF of serum apolipoprotein C-III was performed as described (Wopereis et al 2003). Transferrin N-glycan analysis by MALDI TOF MS was performed as described in Sturiale et al 2008 andPapac et al 1996 (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…IEF of serum apolipoprotein C-III was performed as described (Wopereis et al 2003). Transferrin N-glycan analysis by MALDI TOF MS was performed as described in Sturiale et al 2008 andPapac et al 1996 (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Transferrin isoelectric focussing (TIEF) and apolipoprotein-C isoelectrophoresis (ApoC-III IEF) were carried out as screening for glycosylation disorders by standard methods (see Supplementary Data). 34,35 Molecular genetic studies Genomic DNA was extracted from peripheral blood lymphocytes using standard salting out procedures. 36 Genotyping was performed by using the Affymetrix GeneChip Mapping 10K 2.0 array or the Affymetrix NspI 250K SNP array.…”
Section: Metabolic Investigationsmentioning
confidence: 99%
“…Apolipoprotein CIII (apo CIII) is a small glycoprotein of mass 8.7 kDa that has one mucin type O-linked glycosylation site and has been shown to be useful in detecting defective core 1 mucin type O-glycosylation [17].…”
Section: Current Diagnostic Strategiesmentioning
confidence: 99%